Cognitive impacts of group dynamics: exploring memory errors in observing actions by familiar and unfamiliar individuals - Yue, Yaqi; Wang, Lijuan (Current psychology (New Brunswick, N.J.), 2024)
Observing the behavior of others can lead to false memories of self-expression –observation-inflation effect. Previous research has highlighted a significant reduction in memory errors when a specific action is executed by individuals from an external group. However, the impact of relationships among members within the same group on this type of memory error remains an unresolved question. In Experiment 1, participants were instructed to observe actions performed by both familiar and unfamiliar individuals. The observation-inflation effect was evident in both instances in memory tests conducted two weeks later. However, actions performed by familiar individuals were more likely to induce confusion regarding the identity of the action’s subject in individual recollections. Experiment 2 utilized electroencephalographic oscillations in the Mu frequency range (8–13 Hz) over the sensorimotor cortex as an index of motor simulation. By comparing the power of Mu frequency during the observation of actions performed by familiar and unfamiliar individuals, the study found a decrease in Mu power when individuals observed actions of familiar individuals compared to those performed by unfamiliar individuals. This suggests that the actions of familiar individuals enhance the activity of mirror neurons in the individual’s brain. These findings further strengthen our understanding of the mechanisms underlying the observation-inflation effect. Specifically, individuals exhibit a predisposition to engage in more profound simulations of actions performed by familiar individuals, which may be one of the prominent reasons for the heightened observation-inflation effect.